RETRACTED: Linking Financial Development and Environment in Developed Nation Using Frequency Domain Causality Techniques: The Role of Globalization and Renewable Energy Consumption - Mosleh, Sara; Al-Geitany, Souha; Lawrence Emeagwali, Okechukwu; Altuntaş, Mehmet; Agyekum, Ephraim Bonah; Kamel, Salah; El-Naggar, Mohamed F.; Agbozo, Ebenezer (Frontiers in Environmental Science, 2022)
The topic of whether globalization, energy consumption and financial development can substantially reduce emissions during the globalization mode remains unanswered. In this context, this research reveals empirical indication supporting this theoretical discord, assessing the effect of globalization, energy consumption and financial development on the CO2 emissions in Japan utilizing a dataset between 1990 and 2019. The study employed the ARDL and frequency domain causality to probe these relationships. The findings from the ARDL disclosed that globalization and renewable energy contribute to the mitigation of CO2 emissions while fossil fuel, economic growth and financial development caused an upsurge in CO2 in Japan. Furthermore, the frequency domain demonstrated that all the exogenous variables can forecast CO2 mostly in the long-term which implies that any policy initiated for the exogenous variables will impact emissions of CO2. The problems of autocorrelation and heteroscedasticity were also investigated using diagnostic approaches. The results show that the accepted model has no contradictory concerns with heteroscedasticity and autocorrelation, as evidenced by a Chi-square value of higher than 0.10 percent. As a result, Japan has to improve its financial systems and increase its use of renewable energy. Furthermore, Japan needs to restructure its policy regarding globalization since it contributes to the degradation of the environment.